The effect of gravity on hand spatio-temporal kinematic features during functional movements. - Anna Bucchieri; Federico Tessari; Stefano Buccelli; Elena De Momi; Matteo Laffranchi; Lorenzo De Michieli (PLoS ONE)
Understanding the impact of gravity on daily upper-limb movements is crucial for comprehending upper-limb impairments. This study investigates the relationship between gravitational force and upper-limb mobility by analyzing hand trajectories from 24 healthy subjects performing nine pick-and-place tasks, captured using a motion capture system. The results reveal significant differences in motor behavior in terms of planning, smoothness, efficiency, and accuracy when movements are performed against or with gravity. Analysis showed that upward movements (g-) resembled transversal ones (g0) but differed significantly from downward movements (g+). Corrective movements in g+ began later than in g- and g0, indicating different motor planning models. Velocity profiles highlighted smoother movements in g- and g0 compared to g+. Smoothness was lower in g+, indicating less coordinated movements. Efficiency showed significant variability with no specific trends due to subjective task duration among subjects. This study highlights the importance of considering gravitational effects when evaluating upper-limb movements, especially for individuals with neurological impairments. Planning metrics, including Percent Time to Peak Velocity and Percent Time to Peak Standard Deviation, showed significant differences between g- and g0 compared to g+, supporting Fitts' law on the trade-off between speed and accuracy. Two novel indications were also introduced: the Target Position Error and the Minimum Required Tunnel. These new indicators provided insights into hand-eye coordination and movement variability. The findings suggest that motor planning, smoothness, and efficiency are significantly influenced by gravity, emphasizing the need for differentiated approaches in assessing and rehabilitating upper-limb impairments. Future research should explore these metrics in impaired populations to develop targeted rehabilitation strategies.